Breaking Resilience for a Sustainable Future: Thoughts for the Anthropocene - Glaser, Marion; Plass-Johnson, Jeremiah G.; Ferse, Sebastian C. A.; Neil, Muhammad; Satari, Dewi Y.; Teichberg, Mirta; Reuter, Hauke (Frontiers in Marine Science, 2018)
Strong resilience of a system usually enables the protection of a status quo. Most resilience studies assume that resilience-building is the central objective of sustainability work. Even though transformation has become a central theme in the development and social-ecological debates, questions surrounding the weakening resilience of undesired system states are rarely analyzed. We suggest that resilience studies not only serve to protect systems and feedbacks we want to maintain, but may also help to understand and overcome chronic, undesirable, - and thus wicked - resilience. This contribution focuses on reef fisheries in the Spermonde Island Archipelago in Indonesia, based on social and ecological studies between 2004 and 2016. We identify a number of interlocking wickedly resilient vicious cycles as predominant drivers of the poverty and exploitation of fishing households and the overexploited, polluted and degraded state of the coral reefs that fishers’ livelihoods depend on. We argue that, more often than not in the Anthropocene, breaking resilience has a central role in the pursuit of sustainable human-nature relations. Therefore, the link between the resilience and the transformation debates needs to be much more explicitly made. Breaking interlocking, wicked resilience at multiple levels is needed to move towards sustainable human-nature relations from the local to the global level. There are lacunae in debate, literature, and research practice as to when, where and how wicked resilience might need to be weakened. A more complete resilience lens is particularly needed under Anthropocene conditions to support the unmaking of chronically resilient, anthropogenic systems.